2019
DOI: 10.3389/fphys.2019.00757
|View full text |Cite
|
Sign up to set email alerts
|

A TR(i)P to Cell Migration: New Roles of TRP Channels in Mechanotransduction and Cancer

Abstract: Cell migration is a key process in cancer metastasis, allowing malignant cells to spread from the primary tumor to distant organs. At the molecular level, migration is the result of several coordinated events involving mechanical forces and cellular signaling, where the second messenger Ca 2+ plays a pivotal role. Therefore, elucidating the regulation of intracellular Ca 2+ levels is key for a complete understanding of the mechanisms controlling cellular migration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 131 publications
0
63
0
Order By: Relevance
“…We further evaluated how the presence of AQP2 would modulate NHE1 activity. Keeping in mind that (a) NHE1 activity is highly modulated by Ca 2+ (Shi et al, ), (b) we have recently shown a physical interaction between AQP2 and the Ca 2+ channel TRPV4 in AQP2‐RCCD 1 cells (Pizzoni et al, ), and (c) increasing evidence supports the understanding that in some cell types, TRPV4 would be a key regulator of Ca 2+ signals by mediating the mechanotransduction shaping cell migration (Canales et al, ), we investigated whether AQP2 could modulate NHE1 activity through its Ca 2+ channel partner TRPV4. To test this hypothesis, we measure NHE1 activity after blocking either AQP2 with 100 μM HgCl 2 or TRPV4 with 1 μM HC‐067047.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We further evaluated how the presence of AQP2 would modulate NHE1 activity. Keeping in mind that (a) NHE1 activity is highly modulated by Ca 2+ (Shi et al, ), (b) we have recently shown a physical interaction between AQP2 and the Ca 2+ channel TRPV4 in AQP2‐RCCD 1 cells (Pizzoni et al, ), and (c) increasing evidence supports the understanding that in some cell types, TRPV4 would be a key regulator of Ca 2+ signals by mediating the mechanotransduction shaping cell migration (Canales et al, ), we investigated whether AQP2 could modulate NHE1 activity through its Ca 2+ channel partner TRPV4. To test this hypothesis, we measure NHE1 activity after blocking either AQP2 with 100 μM HgCl 2 or TRPV4 with 1 μM HC‐067047.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, CaM binds to high‐ and low‐affinity sites and blocks an autoinhibitory site, thereby activating NHE1 (Shi et al, ). In addition, increasing evidence demonstrates the role of several members of the TRP Ca 2+ channel superfamily, including TRPV4, in the mechanotransduction during cell migration (Canales et al, ). We have previously demonstrated a physical association between AQP2 and TRPV4 in modulating Ca 2+ transients in CCD cells (Pizzoni et al, ) and here we observe that blocking AQP2 or TRPV4 reduces significantly and to a similar extent NHE1 activity in the lamellipodia of migrating cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRP channels are non-selective cation channels that can be activated by different stimuli such as pH variations, temperature and pressure among others [71,72]. Since TRP channels are involved in migration and invasiveness, they contribute to the metastatic process in different tumors [73]. Ca 2+ influx through TRPCs also occurs and promotes either cell proliferation or apoptosis, depending on TRPC subtype.…”
Section: Transient Receptor Potential (Trp) Channelsmentioning
confidence: 99%